Diagnostic performance of contrast-enhanced CT combined with contrast-enhanced MRI for colorectal liver metastases: a case-control study - Luxian Zhang; Luna Bai (BMC Gastroenterology)
Abstract Background Colorectal liver metastases (CRLM) are a major determinant of prognosis in colorectal cancer (CRC) patients. Their early and accurate detection is essential for appropriate therapeutic planning and improving survival outcomes. Purpose To evaluate the diagnostic capabilities of contrast-enhanced computed tomography (CT) and contrast-enhanced magnetic resonance imaging (MRI) in detecting colorectal liver metastases. Materials and methods We employed a case-control design to compare patients with histologically confirmed liver metastases against a control group without the condition. A total of 85 patients in each group were selected and retrospectively matched based on relevant factors. All subjects underwent both contrast-enhanced CT and MRI. The diagnostic performance of these imaging modalities was assessed by analysing sensitivity, specificity, positive and negative predictive values, and radiologists’ diagnostic confidence. Kappa statistics were used to evaluate inter-observer agreement. All MRI scans were performed using a 3-Tesla (3-T) MRI scanner to ensure high-quality imaging and detailed lesion characterization. And all the scans were reviewed by two radiologists. Results The combination of contrast-enhanced CT and MRI demonstrated a statistically significant improvement in sensitivity (90.6% for MRI alone vs. 96.5% for combined modalities) and specificity (95.3% for MRI alone vs. 98.3% for combined modalities). Positive and negative predictive values were similarly enhanced. Radiologists’ diagnostic confidence was higher with combined imaging, achieving a ‘very high’ confidence level in 78.8% of cases compared with 64.7% for MRI alone. The inter-observer agreement reached ‘almost perfect’ status with the combined approach. Conclusion The integration of contrast-enhanced CT with MRI significantly enhanced the diagnostic accuracy for colorectal liver metastases, representing a valuable tool for the preoperative evaluation of patients with CRC. Clinical trial number Not applicable.